(untitled) (Research, Society and Development, 2022)
This article aimed to investigate and analyze the mechanisms used in the inspection of public contracts of a Federal University in Minas Gerais and of some federal public agencies and, in view of the results, to develop a customized tool that provides security, efficiency, training, interaction and productivity. An efficient management of public resources is a basic principle to achieve the interests of a society. The study employed consultation and application of a qualitative questionnaire with open and closed questions, respectively, with the researched entities, as well as secondary research of studies related to the theme and current legislation for data analysis. The results point to: a) deficiency in the process of training and fiscal management; b) need to modernize the tools used since the last 10 years, to register the inspection c) low or non-existent involvement of inspectors regarding the collection of the evaluation of the public that uses the contracted object. In view of the results presented, a fiscal support software will be developed with a focus on contract management that can be used by federal public universities or other federal public agencies.